The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12974-019-1674-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular biomarkers in multiple sclerosis

Abstract: Multiple sclerosis (MS) is an inflammatory-neurodegenerative disease of the central nervous system presenting with significant inter- and intraindividual heterogeneity. However, the application of clinical and imaging biomarkers is currently not able to allow individual characterization and prediction. Complementary, molecular biomarkers which are easily quantifiable come from the areas of immunology and neurobiology due to the causal pathomechanisms and can excellently complement other disease characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
162
0
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(171 citation statements)
references
References 144 publications
2
162
0
7
Order By: Relevance
“…MS patients showed an intrathecal production of IgG, IgM, and IgA (Lolli et al, 1989); about 95% of the MS patients displayed IgG OCBs (Link, 1978;Villar et al, 2005), and around 40% also showed intrathecal IgM production (Villar et al, 2005), while CSF IgA synthesis was only occasionally observed (in 13% of cases) (Link and Müller, 1971;Leary et al, 2000). Therefore, IgG (predominantly IgG1), and IgM are considered the major contributors to the OCB formation in the CSF (Ziemssen and Ziemssen, 2005;Ziemssen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MS patients showed an intrathecal production of IgG, IgM, and IgA (Lolli et al, 1989); about 95% of the MS patients displayed IgG OCBs (Link, 1978;Villar et al, 2005), and around 40% also showed intrathecal IgM production (Villar et al, 2005), while CSF IgA synthesis was only occasionally observed (in 13% of cases) (Link and Müller, 1971;Leary et al, 2000). Therefore, IgG (predominantly IgG1), and IgM are considered the major contributors to the OCB formation in the CSF (Ziemssen and Ziemssen, 2005;Ziemssen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sclerosis (MS) is a chronic inflammatory demyelinating and neurodegenerative disease that affects the central nervous system (CNS). The presence of oligoclonal bands (OCBs) in the cerebrospinal fluid (CSF), but not within the serum, is a strong indicator of intrathecal antibody synthesis (Ziemssen et al, 2019) and has been considered a hallmark of MS that contributes to the diagnosis (Thompson et al, 2018). Immunoglobulin G (IgG) and IgM antibodies are major contributors to the OCBs formation in the CSF (Ziemssen and Ziemssen, 2005;Ziemssen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it has been shown that the ability to select appropriate responses in close succession is predicted by concentrations of serum neurofilament light chain (sNfl) ( 29 ). This is of high relevance because there are strong links between the sNfl and the integrity of the white matter structure ( 30 34 ), particularly in MS ( 35 , 36 ). It has been shown ( 37 ) that MS patients performed considerably worse than healthy control participants and that the deficits shown by the patients are very likely not due to simple motor deficits.…”
Section: Cognitive–cognitive Dual Tasking Assessment In the Context Omentioning
confidence: 99%
“…Several neurological-clinical domains should be part of the quantitative assessment of individual neurological FS (e.g., cognition, walking) as eg. imaging (magnetic resonance imaging, ocular coherence tomography) and electrophysiological procedures, patient-reported outcomes (PRO), new molecular (e.g., neurofilament light chain) and digital biomarkers (D'Amico et al, 2019;Ziemssen et al, 2019;Inojosa et al, 2020a). The ability to walk is an important prerequisite to participate autonomously in daily life.…”
Section: Introductionmentioning
confidence: 99%